An Evaluation of the Spontaneous Proliferation of Peripheral Blood Mononuclear Cells in HTLV-1-Infected Individuals Using Flow Cytometry. (25th September 2011) - Pinto, Lorena Ana; Galvão Castro, Bernardo; Soares, Milena Botelho Pereira; Grassi, Maria Fernanda Rios
Abstract : The spontaneous proliferation of peripheral blood mononuclear cells (PBMCs) is a hallmark of the human T-lymphotropic virus (HTLV) type-1. Cell proliferation is usually measured using a [ 3 H]thymidine incorporation assay. This study aims to quantify the spontaneous proliferation of PBMCs using flow cytometry. PBMCs were cultured for 24 to 120 hours in the presence of 5, 6-carboxyfluorescein diacetate succinimidyl ester (CFSE). For comparison, PBMCs were also cultured with [ 3 H]thymidine. The cutoff values for spontaneous proliferation were >0.06 for the division index and >5.8% for the percentage of divided cells. Sixty-two percent of HTLV-1-infected individuals presented spontaneous proliferation of PBMCs, which was detected in the first 24 hours. Moreover, proliferation was detected in CD4 + and CD8 + T-lymphocyte subsets. A positive correlation was found between the division index and [ 3 H]thymidine incorporation. This method may prove useful to better understand the phenomenon of spontaneous proliferation of PBMC of patients infected with HTLV-1.